BAG2-Mediated Inhibition of CHIP Expression and Overexpression of MDM2 Contribute to the Initiation of Endometriosis by Modulating Estrogen Receptor Status - Chen, Li-Juan; Hu, Bin; Han, Zhi-Qiang; Zhu, Jian-Hua; Fan, Xu; Chen, Xue-Xing; Li, Zi-Ping; Zhou, Hao (Frontiers in Cell and Developmental Biology, 2021)
Endometriosis is an estrogen-dependent gynecological disease primarily affecting women of childbearing age, which gives rise to pelvic pain calling for multiple operations, and sometimes leading to infertility. However, the aetiology of endometriosis remains poorly understood. In this study we investigated the roles of two Ubiquitin E3 Ligases, namely hsc70-interacting protein (CHIP) and mouse double minute 2 (MDM2), in the abnormal estrogenic activity in endometriosis. We first collected endometrial tissues from 91 cases of endometriosis and 78 cases of uterine myomas. Next, we established a murine endometriosis model by ectopic endometrial tissue implantation. In other studies , we isolated human endometrial stromal cells (HESCs) were isolated from the endometrial tissues, and performed HA- or FLAG-immunoprecipitation assays and immunoblotting with an anti-ubiquitin antibody to test the interactions among BAG2, CHIP, MDM2, estrogen receptor α (ERα), and ERβ. The expression of ERα was downregulated while that of ERβ, BAG2, and MDM2 was upregulated in human endometriosis and in the mouse model. CHIP degraded ERβ instead of ERα via the ubiquitin-proteasome pathway, while BAG2 impaired the CHIP-mediated degradation of ERβ in cultured HESCs derived from human endometriosis. The degradation of ERα by MDM2 in cultured endometriosis-HESCs also occurred through the ubiquitin-proteasome pathway. Knockdown of both BAG2 and MDM2 alleviated the development of endometriosis in mice. Our findings suggest that the interference of BAG2 and MDM2 may have therapeutic effects in endometriosis. Understanding better the molecular mechanisms underlying the regulation of the abnormal estrogenic activity in endometriosis is crucial for the advancement of targeted therapeutic strategies.